A Contrastive Analysis of Language Style in Traditional Javanese and Japanese Children’s Songs and Their Educational Values from an Ethnostylistic Perspective - Kurwidaria, Favorita; Budilestari, Eni Sri; Rahadini, Astiana Ajeng; Wijayanti, Kenfitria Diah; Pribadi, Nirbito Hanggoro; Said, Dewi Pangestu; Veronika, Prima; Setiyaka, Gagah Wahyu (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2026)
This study analyses the language style in the lyrics of traditional Javanese children’s songs (tembang dolanan) and Japanese children’s songs (warabe uta) through contrastive analysis from an ethnostylistic perspective. This study aims to describe the forms of language style used and to reveal their similarities and differences based on their cultural backgrounds. The study used a qualitative method using content analysis by contrasting Javanese and Japanese children’s song lyrics. Data were collected through document analysis of song lyrics, supported by interviews with instructors from Japan and experts in the Javanese language. The data, validated through source triangulation and strengthened by Focus Group Discussions (FGDs), were analysed using James P. Spradley’s ethnographic stages, including domain, taxonomic, componential, and cultural theme analysis. The findings indicate that language style in both Javanese and Japanese children’s song lyrics is constructed through rhyme, repetition, lexical choices related to nature, animals, and plants, as well as the use of figurative language (metaphor, personification, hyperbole, and simile) and symbolism. These stylistic choices collectively support the construction of meaning and the transmission of educational values within their respective cultural contexts. Therefore, this study contributes to the development of contrastive linguistic analysis by demonstrating that such analysis can extend beyond structural comparison to integrate specific analytical perspectives, such as ethnostylistics. In addition, it offers insights into the exploration of stylistic language use in creative texts, particularly song lyrics, which may serve as alternative media for character education in children. Future research is recommended to expand the corpus by including a wider range of children’s songs across cultures and to examine their implementation in deeper learning contexts involving culturally based creative texts.